2016
DOI: 10.1016/j.bpc.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular diffusion controls aggregation of the PAPf39 peptide

Abstract: The 39-residue fragment of human prostatic acidic phosphatase (PAP) is found in high concentrations in semen and easily form fibrils. Previous work has shown that fibrillization is accelerated with a deletion of the first 8, mostly charged residues and it was hypothesized that fibrillization depended on the dynamics of these peptides. To test this hypothesis we have measured the intramolecular diffusion of the full length and 8-residue deletion peptides at two different pHs and found a correlation with fibrill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…The ThT fluorescence curve resulted in a sigmoidal pattern with a prominent lag phase till 24 h corresponding to the nucleation stage, and was later followed by the exponential increase and plateau fluorescence representing oligomerization and fibril maturation, respectively. These aggregation kinetics appeared similar to the nucleation-dependent polymerization model for amyloidogenic proteins [32] as observed previously for PAP f39 aggregation [7,33,34,35].…”
Section: Resultssupporting
confidence: 84%
“…The ThT fluorescence curve resulted in a sigmoidal pattern with a prominent lag phase till 24 h corresponding to the nucleation stage, and was later followed by the exponential increase and plateau fluorescence representing oligomerization and fibril maturation, respectively. These aggregation kinetics appeared similar to the nucleation-dependent polymerization model for amyloidogenic proteins [32] as observed previously for PAP f39 aggregation [7,33,34,35].…”
Section: Resultssupporting
confidence: 84%
“…Although direct ion binding has been proposed to influence aSyn aggregation rates, the ion binding strength does not correlate with aggregation rates observed 33 IDPs rely on their ability to be highly dynamic and flexible to probe different conformational space allowing maintenance of their solubility and function. When the reconfiguration rates of the protein backbone are retarded this can lead to aggregation 17,[34][35][36][37][38] . For protein association and aggregation to occur, the proteins must firstly be in an aggregation prone conformation, and secondly must be stable for long enough for interactions to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Threonine may decrease D and therefore decrease the rate by increasing barriers to dihedral angle motion, and its bulkier side-chain compared to Ala could slow the rate by increasing r 2 . 27 Other interesting examples of using the technique of Trp-Cys contact quenching were the measurements of the rate of intramolecular contact in four different loops along the chain in α-synuclein, 29 in a fragment of human prostatic acidic phosphatase (PAP) showing that the full-length peptide diffuses much faster than the truncated peptide, 30 in protein L showing surprisingly low diffusion rates, 31,32 and in Syrian hamster and rabbit prion proteins at different pH values and concentration of denaturants. 33 The results presented above showed that some directly induced photochemical processes can be used for studying the kinetics of intramolecular-contact formation in peptides and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Other interesting examples of using the technique of Trp-Cys contact quenching were the measurements of the rate of intramolecular contact in four different loops along the chain in α-synuclein, in a fragment of human prostatic acidic phosphatase (PAP) showing that the full-length peptide diffuses much faster than the truncated peptide, in protein L showing surprisingly low diffusion rates, , and in Syrian hamster and rabbit prion proteins at different pH values and concentration of denaturants …”
Section: Introductionmentioning
confidence: 99%